Kinesiology tape length and ankle inversion proprioception at step-down landing in individuals with chronic ankle instability. Issue 9 (September 2021) - Yu, Ruoni; Yang, Zonghan; Witchalls, Jeremy; Adams, Roger; Waddington, Gordon; Han, Jia
Abstract: Objectives: To determine the effect of different lengths of kinesiology tape (KT) on ankle inversion proprioceptive performance in individuals with or without chronic ankle instability (CAI). Design: A repeated measures study. Methods: Fifteen participants with unilateral CAI and fifteen participants with no CAI volunteered. The Ankle Inversion Discrimination Apparatus for Landing (AIDAL) was used to measure ankle proprioceptive acuity. All participants were tested under four KT conditions: no tape (baseline), short tape length (only foot and ankle complex involved), mid length (below the knee) and long length (above the knee) taping. After the baseline test, participants underwent the 3 different taping tests in a random order. Results: Repeated measures ANOVA indicated that, compared to those without CAI, individuals with CAI performed significantly worse across the 4 different conditions (F = 8.196, p = 0.008). There was a significant KT main effect (F = 7.489, p < 0.001) and a significant linear effect (F = 17.083, p < 0.001), suggesting that KT significantly improved ankle proprioceptive performance in landing, and with longer tape length there was greater proprioceptive enhancement. Post-hoc analysis showed that for the CAI group, both mid length ( p = 0.013, 95%CI = −0.063, −0.009) and long length ( p = 0.010, 95%CI = −0.067, −0.011) taping can significantly improve ankle proprioceptive performance compared to no tape, whereas for the non-CAI group, ankle proprioceptive acuity was significantly improved only with long length taping ( p = 0.007, 95%CI = −0.080, −0.015). Conclusions: KT can be used to improve ankle inversion proprioceptive performance during landing in both individuals with and without CAI and increasing tape length may achieve greater proprioceptive improvement.